A method of improving oar efficiency - Brearley, M. (ANZIAM Journal, 2008)
In boats used for competitive rowing it is traditional for the rowers to use strokes in which the angle between the oar shaft and the perpendicular to the hull centre line is much greater at the catch than it is at the end of the power stroke. As a result, the oar blade is even more inefficient in its action at the catch than it is at the end of the power stroke. This paper shows how boat performance in a race would be improved by reducing the difference in these starting and finishing angles. The claim of improved race performance is supported by a detailed investigation of the dynamics involved in the case of a particular coxless pair whose performance has been recorded by the Australian Institute of Sport. We also suggest an easy way to make the necessary change in boat design.